Clinicopathological features of diabetic and nondiabetic renal diseases in type 2 diabetic patients with nephrotic-range proteinuria. Issue 36 (September 2017) - Lee, Yu Ho; Kim, Ki-Pyo; Kim, Yang Gyun; Moon, Ju-Young; Jung, Su Woong; Park, Eunji; Kim, Jin Sug; Jeong, Kyung-Hwan; Lee, Tae Won; Ihm, Chun-Gyoo; Jo, Young-Il; Choi, Hoon-Young; et al.
Abstract : Abstract: Heavy proteinuria with or without features of nephrotic syndrome is associated with many primary and systemic diseases. For diabetic patients, distinguishing nondiabetic renal disease (NDRD) from diabetic nephropathy (DN) is important in choosing treatment modalities and determining renal prognosis. However, clinical relevance of heavy proteinuria is inconsistent with clinical DN assessments. This study investigated the clinicopathological features and renal outcomes of DN and NDRD in type 2 diabetic patients with nephrotic-range proteinuria. We enrolled 220 cases of type 2 diabetic patients who underwent renal biopsy. They were grouped according to the presence of nephritic-range proteinuria and pathological features. Baseline characteristics, laboratory findings, types of pathological diagnosis, and renal outcomes were analyzed in patients with heavy proteinuria. Upon kidney biopsy, 129 patients (58.6%) showed nephritic-range proteinuria. Patients with heavy proteinuria (an average urine protein-to-creatinine ratio of 10, 008 ± 7307 mg/gCr) showed lower serum albumin levels and higher total cholesterol levels, but did not show any difference in age, duration of diabetes, renal function, or the presence of retinopathy compared with those with mild-to-moderate proteinuria (an average urine protein-to-creatinine ratio of 1581 ± 979 mg/gCr). Renal biopsy revealed that the prevalence of NDRD was 37.2% in patients with heavy proteinuria, which was significantly lower than that in patients with mild-to-moderate proteinuria (63.7%). The most common pathological types of NDRD were membranous nephropathy (41.7%), IgA nephropathy (14.6%), and minimal change disease (10.4%). NDRD patients showed lower prevalence of diabetic retinopathy and better kidney function irrespective of proteinuria. Immunosuppressive treatment was administered more frequently in patients with heavy proteinuria (56.3%) compared with patients with mild-to-moderate proteinuria (20%) because of the pathological differences according to the amount of proteinuria. Renal outcomes were significantly worse in patients with DN than in patients with NDRD. DN patients with heavy proteinuria exhibited different prevalence of NDRD and worse prognosis. Renal biopsy in type 2 diabetic patients should be more extensively considered to accurately diagnose NDRD, guide further management, and predict renal outcomes, especially in patients with nephrotic-range proteinuria. Abstract : Supplemental Digital Content is available in the text